Mitochondrial haplogroup A2 is associated with increased COVID-19 mortality in an admixed Brazilian population - Gustavo Medina Tavares; Bruna Oliveira Missaggia; Nathan Araujo Cadore; Renan César Sbruzzi; Marilea Furtado Feira; Giovanna Câmara Giudicelli; Bibiana Sampaio de Oliveira Fam; Maira Rodrigues; Márcio Dorn; Tábita Hünemeier; Fernanda Sales Luiz Vianna; Maria Cátira Bortolini (Scientific Reports)
Abstract Mitochondria play a crucial role in cellular respiration and immune responses. Mitochondrial DNA (mtDNA) haplogroups and variants have been associated with various diseases, including COVID-19. This study analyzed complete mtDNA sequences from 467 Brazilian patients with COVID-19 to investigate associations between mtDNA ancestry and mortality risk. Using classical statistical methods and a machine learning model, we identified key contributors to outcomes, with age as the primary risk factor, followed by male sex. Several mtDNA variants—663G, 1736G, 2706G, 3010A, 4248C, 4824G, 8027A, 8794T, and 10873C—were significantly associated with increased mortality risk. Most are characteristic of haplogroup A2, prevalent in populations with Native American ancestry. Notably, the 8027A allele, a non-synonymous substitution (Alanine > Threonine at position 148 of Cytochrome C Oxidase II), was predicted to be potentially damaging and emerged as the most significant marker. Rather than being disease-causing, these variants may amplify risk through interactions with other genetic, environmental, and clinical factors. Our findings emphasize that mtDNA variants and haplogroups are not phenotypically neutral and could serve as biomarkers of COVID-19 severity. Genetic studies prioritizing Indigenous populations and their descendants, who may be particularly susceptible to certain viruses, are urgently needed, especially given the predominant focus on European populations.